Auditory pathway features determined by DTI in subjects with unilateral acoustic neuroma - Kurtcan, Serpil; Alkan, Alpay; Kılıçarslan, Rukiye; Bakan, Ayşe Ahsen; Toprak, Hüseyin; Aralaşmak, Ayşe; Aksoy, Fadlullah; Koçer, Abdülkadir (Springer Heidelberg, 2016)
In the studies concerning the pathology of the auditory pathway in the vestibulocochlear system, few use advanced neuroimaging applications of magnetic resonance imaging (MRI) such as diffusion tensor imaging (DTI). Those who did use reported DTI changes only at the lateral lemniscus and inferior colliculus level. The aim of our study was to determine diffusion changes in the bilateral auditory pathways of subjects with unilateral acoustic neuroma (AN) and compare them with healthy controls. A total of 15 subjects with unilateral AN along with 11 controls underwent routine MRI and DTI. Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values obtained from the lateral lemniscus, inferior colliculus, corpus geniculatum mediale, and Heschl's gyrus of the auditory pathway were then compared. The subjects' ADC values measured from the contralateral side were significantly higher at the lateral lemniscus, inferior colliculus, and corpus geniculatum mediale compared with those of the controls. Also, decreased FA values were noted at the inferior colliculus for both the contralateral and ipsilateral sides. The highest ADC values were detected in the inferior colliculus of the auditory pathway. In the auditory pathway of subjects with AN, the contralateral side is more affected than the ipsilateral side, the most affected region being the inferior colliculus. DTI is an advanced neuroimaging technique that can be used to determine the presence of microstructural damage to the auditory pathway in subjects with AN, whereas conventional MRI is not sensitive enough to detect damage.
WOS: 000389606200007
PubMed ID: 25813527
Keywords: Acoustic Neuroma; DTI; Auditory Pathway